Drugs, Crime, and Urban Trial Court Management: The Unintended Consequences of the War on Drugs - Martin, John A (2015)
The cultivation, distribution, sale, and consumption of illicit drugs have profoundly affected all aspects of American life. During the past few years, a proliferation of popular books, magazine articles, and scholarly publications have focused on America's drug problem. Moreover, public opinion surveys conducted throughout the 1980s consistently show that Americans consider drug abuse to be among the most important problems confronting their local communities and their nation. The public perception is well-founded, since detailed general population studies have revealed that considerable illegal drug use is occurring among all segments of American society. In 1986, for example, the United States imported approximately 11,000 tons of marijuana, 165 tons of hashish, 138 tons of cocaine and its derivatives, and seven tons of heroin and other opium derivatives. Thousands of tons of domestic marijuana and tens of millions of illicit doses of synthetic narcotics such as PCP, methadone, Demerol, Darvon, and Talwin were also consumed each year. Cocaine, consumed at least occasionally by seven to thirteen million Americans, is by itself a $20 billion component of the $50 billion drug industry